Fear of the Aquatic Environment in Learning Swimming: Causes, Effects, and Learning Methodologies - Diana Coelho; Paulo Eira; António Azevedo (Education Sciences, 2025)
In the swimming context, practitioners show difficulties in learning its basic skills, and the emotional factor seems to be one of the triggers for these complications, with “fear” standing out as one of the most studied emotions due to its cognitive reactive nature associated with survival mechanisms. This emotional response can hinder the learning process in swimming, potentially leading to disengagement or dropout. The present study aimed to analyze the causes that lead to fear of the aquatic environment, its effects on learning swimming, and how swimming coaches can intervene to help overcome this fear. Direct observation was used to capture the individuals’ perception of the degree of fear. Subsequently, semi-structured interviews were conducted to analyze an intervention aimed at reducing the fear of water, followed by a corresponding content analysis. The fear of water is commonly associated with anxiety, panic, and muscle tension. The role of the swimming instructor is crucial, as their teaching approach significantly influences the swimmer’s emotional response, particularly in fostering a sense of security. The use of playful activities proves effective in helping children adapt, overcoming the limitations posed by the fear of water. Recognizing students’ fears allows instructors to structure swimming lessons effectively, helping students overcome their emotional barriers. Therefore, introducing children to the aquatic environment at an early age contributes to this goal.